Tinjauan Yuridis Pengawasan Dan Pengendalian SertaPemanfaatan Minuman Beralkohol Tradisional YangBeredar Pada Konsumen Oleh Dinas PerdaganganDan Kesehatan Kabupaten Sukoharjo(Studi Terhadap Minuman Keras Tradisional Ciu) - Hidayah, Reyzza Claudya; , Wardah Yuspin, S.H.,M.Kn.,Ph.D (2017)
This research aims to know the form of regulation related to the regulation of traditional liquor distribution (ciu), to know the form of supervision and control conducted by related institutions against the circulation of traditional alcoholic beverages (ciu) In Sukoharjo, and to know the form of utilization made by related institutions against traditional alcoholic beverages (ciu) in order to become a positive product and can be utilized by the community legally. The approach method that I use is the empirical juridical approach. The type of research used by the authors in this study is to use descriptive research type. Location of research in Dinas Perdagangan and Dinas Kesehatan Kabupaten Sukoharjo. Based on the results of research and discussion it can be concluded that the form of empowerment and utilization of alcoholic processed products, one of them in the form of raw materials of the pharmaceutical industry. Such empowerment and utilization will directly benefit the community, especially processed alcoholic product producers from an economic point of view.